Clostridium Spores with Ribbon-like Appendages - Rode, L. J. (1967)
Spores of Clostridium sp. N1 are characterized by numerous broad ribbon-like appendages attached to one end. The appendages are two to three times the length of the spore and, at their maximal dimension, may be two-thirds the width of the spore. They are attached to the spore body by a common trunk which is continuous with the outer spore coat. Each appendage is a multilayered structure and is enclosed in an amorphous material. Details of spore and appendage formation are described, and appendage ultrastructural features are presented. The function of the appendages is not known.